Twenty-six new species of Saussurea (Asteraceae, Cardueae) from the Qinghai-Tibetan Plateau and adjacent regions - Chen, Yousheng; Yuan, Qian (Phytotaxa, 2015)
Twenty-six new species of Saussurea (Asteraceae, Cardueae) from the Qinghai-Tibetan Plateau and adjacent regions are described and illustrated. Our molecular phylogenetic analysis based on the nuclear ribosomal DNA internal transcribed spacer (ITS) and two chloroplast DNA fragments (trnL-F and psbA-trnH) has shown that most of the new species are well recognized in the molecular tree, with their taxonomic affinities also largely revealed.